Pemanfaatan Situs Web Youtube Sebagai Wahana Promosi Dan Sumber Pendapatan Tambahan Bagi Pemerintah Desa - DN, Johan Eka Wijaya; Okta, Jumdapi (Universitas Multi Data Palembang, Fakultas Ilmu Komputer dan Rekayasa, 2021)
The era of globalization has brought rapid developments ininformation and communication technology, including the field ofgovernment, one of which is village government. One of the mostinteresting information and communication technology products to takeadvantage of in village government is the YouTube website. In theutilization of media, creativity and also careful planning considerationsare needed from staff who are trusted in managing the account. In fact,many village government staff use the youTube website without carefulconsideration and planning. Tanjung Baru Village is one of the villageslocated in East Baturaja District of Ogan Komering Ulu Regency. Thisvillage is one of the leading, competitive and potential villages. In theprocess of advancing and developing tanjung Baru village assets nowhave village owned enterprises (BUMDes). Business entities that arebeing developed are BUMDes Tourism Village, Soundsytem / OrgenServices, and Buffet Services, chairs and tents. But nowadays theseassets seem difficult to progress and develop. In fact, if it can bemaximized properly then the BUMDes can prosper all staff and villagegovernment devices.